2001
DOI: 10.1562/0031-8655(2001)074<0283:troesb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Elastases Secreted by Fibroblasts in Wrinkle Formation: Implication Through Selective Inhibition of Elastase Activity¶

Abstract: We have previously demonstrated that decreases in skin elasticity, accompanied by increases in the tortuosity of elastic fibers, are important early events in wrinkle formation. In order to study the role of elastases in the degeneration of elastic fibers during wrinkle formation we examined the effects of an inhibitor of skin fibroblast elastase, N-phenethylphosphonyl-L-leucyl-L-tryptophane (NPLT), on wrinkle formation in hairless mice skin following UV irradiation. Dorsal skins of hairless mice were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 19 publications
5
92
0
3
Order By: Relevance
“…4,6,7,9,11,21,22,24,29 Moreover, gene chip analysis indicated a lot of similarities in the comparisons between young versus old skins and our control versus UVB-exposed skins, corroborating the validity of our photodamage or premature photoaging model. Taken together, the present study discloses a novel photodamage model with human skin xenograft that recapitulates mechanisms underlying morphological changes such as wrinkling reported to date, and can be used for the further study of photoaging.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…4,6,7,9,11,21,22,24,29 Moreover, gene chip analysis indicated a lot of similarities in the comparisons between young versus old skins and our control versus UVB-exposed skins, corroborating the validity of our photodamage or premature photoaging model. Taken together, the present study discloses a novel photodamage model with human skin xenograft that recapitulates mechanisms underlying morphological changes such as wrinkling reported to date, and can be used for the further study of photoaging.…”
Section: Discussionsupporting
confidence: 77%
“…5,8,10,11,20 On the other hand, it has been reported that the degeneration of these fibers in chronologically and/or photoaged skin stems from an increase in matrix metalloproteinase-12 (MMP-12) and/or elastase, an elastin-degrading enzyme that is produced and secreted by dermal fibroblasts. [21][22][23][24] To date, the mechanisms underlying the alteration of elastin fibers in photoaged skin including their production, accumulation, and degradation are not fully understood.…”
mentioning
confidence: 99%
“…. elastase 저해제는 피부 주름을 개선하는 작용을 나타 내고, ursolic acid등이 elastase 저해제로 이용되고 있다 16) . 그리고 체내의 elastin을 분해하는 백혈구 과립 효소 중의 하 나로 이상조직에서는 효소의 활성이 극히 높아 조직 파괴에 직접적인 원인이 되어 피부의 주름 및 탄력성 소실을 유발한 다 17) .…”
Section: 서 론unclassified
“…이에 따라 식물 등 천연물로부터 얻어지는 기능성 물질들 을 원료로서 이용하려는 연구가 활발히 진행되고 있 다 [1]. 이러한 요구에 대응하여 천연물 특히 한방소재 또는 약용식물을 중심으로 한 미백효과, 노화억제 및 자외선 차단 기능 등 유용한 소재에 대한 개발이 이루 어지고 있다 [2].…”
Section: 서 론unclassified